Descriptive epidemiology of injuries sustained in National Collegiate Athletic Association men`s and women`s volleyball, 2013-2014 to 2014-2015 - Baugh, C. M.; Weintraub, G. S.; Gregory, A. J.; Djoko, A.; Dompier, T. P.; Kerr, Z. Y. (Sports Health: A Multidisciplinary Approach, 2018)
Background: There were 18,844 volleyball players in the National Collegiate Athletic Association (NCAA) in the 2014-2015 academic year. Little research has examined sex-based differences among these athletes. Purpose: To examine injury epidemiology in NCAA men`s and women`s volleyball athletes. Study Design: Descriptive epidemiology study. Level of Evidence: Level 3. Methods: Injury surveillance data from the 2013-2014 through 2014-2015 academic years were obtained from the NCAA Injury Surveillance Program for 6 men`s and 33 women`s collegiate volleyball teams. Injury rates per 1000 athlete-exposures (AEs) and injury rate ratios (IRRs) with 95% CIs were calculated. Time-loss (TL) injuries resulted in participation restriction for at least 24 hours, and non-time-loss (NTL) injuries resulted in participation restriction of less than 24 hours. Results: Overall, 83 and 510 injuries were reported in men and women, respectively, leading to injury rates of 4.69 and 7.07 per 1000 AEs. The injury rate was greater in women than men (IRR, 1.51; 95% CI, 1.19-1.90). TL injury rates were 1.75 and 2.62 per 1000 AEs for men and women, respectively. The ankle was the most commonly injured body part among TL injuries (men, 25.8%; women, 24.3%); the knee was the most commonly injured body part among NTL injuries (men, 25.5%; women, 16.3%). Among TL injuries, common diagnoses included sprains (men, 25.8%; women, 31.2%) and concussions (men, 19.4%; women, 14.8%). Most TL concussions were due to ball contact (men, 83.3%; women, 53.6%). Compared with men, women had a greater NTL overuse injury rate (IRR, 3.47; 95% CI, 1.61-7.46). Compared with women, men had a greater TL injury rate associated with ball contact (IRR, 2.24; 95% CI, 1.07-4.68). Conclusion: There are differences in injury patterns and rates between male and female intercollegiate volleyball players. Although a limited-contact sport, a notable number of concussions were sustained, mostly from ball contact. Clinical Relevance: Understanding injury patterns may aid clinicians in injury diagnosis, management, and prevention.